To solve the given quadratic equation using square roots, we start by simplifying it. The equation is:
\[ -9 + (x - 3)^2 - 4 = -4 \]
Let's simplify the left side:
-
Combine constants on the left: \[ -9 - 4 = -13 \] So we rewrite the equation as: \[ -13 + (x - 3)^2 = -4 \]
-
Now, add 13 to both sides: \[ (x - 3)^2 = -4 + 13 \] \[ (x - 3)^2 = 9 \]
-
Next, take the square root of both sides: \[ x - 3 = \pm 3 \]
-
Now solve for \(x\):
- For the positive case: \[ x - 3 = 3 \implies x = 6 \]
- For the negative case: \[ x - 3 = -3 \implies x = 0 \]
Thus, the solutions are \(x = 6\) and \(x = 0\).
Finally, we represent this as a set of solutions: \[ {6, 0} \]
However, none of the given response options match this answer. There might be a mistake in the options or in the question provided.
Would you like to solve a different problem or clarify anything?